DEVELOPING ISLAMIC CONTENT-BASED MATERIALS IN TEACHING VOCABULARY AT ENGLISH DEPARTMENT OF TARBIYAH AND TEACHER TRAINING FACULTY OF IAIN BATUSANGKAR - Hendra Eka Putra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
Due to the limited sources of Vocabulary teaching materials, the researcher was eager to design a model of vocabulary materials assumed needed by te students for their daily conversation. The design was a Research and Development applying descriptive procedure of three model suggested by Borg and Gall (1983) who propose three ways of developing a model of teaching material, namely: procedural, conceptual, theoretical.” Then, he followed the research procedure by Sugiyono (2007: 298) suggesting ten steps of a research and development: (1) identifying research problem, (2) collecting information, (3) designing the product, (4) validating the design, (5) revising the design, (6) testing the product , (7) revising the product, (8) applying the design, (9) re-revising the product , and (10) publishing the prooduct. In validating the model, he asked some comments from experts. Because of limited time and other reasons of doing the research, he just applied the step 1 up to 4. Based on the validation result, it could be concluded that the model had fulfilled the criteria both content and construct validity.